An Empirical Review of Role of Education Technology Drivers (EDUTECH) on Education in Emergencies (EiE) Classroom/Non-Classroom Outcomes for Marginalized Countries: The Somalia Perspective - Abdifatah Osman , Hussein (Journal of Education and Practice, 2023)
Purpose: The aim of this essay is to provide a desktop review of existing empirical evidence themes on the necessity and use of education technology for continuity of education in emergencies (EiE) in marginalized countries. The essay aims to provide a summary into how EDUTECH can be leveraged to maintain continuity of education for most marginalized regions in Somalia. Methodology: The empirical review methodology of this essay was borrowed from the Cochrane collaboration rapid assessments framework (Garrittyet al., 2020). The researcher adopted this methodology because it allows for a rigor filled and systemic technique while allowing the scoping narrow enough in a short time, necessary for this assignment Results: A focus on Emergencies (EiE) settings dependent on EDUTECH adoption variable encompassed a cycle of anticipation, response, and recovery on the tenets of how education technology drivers can be harnessed to emancipate Education in Emergencies (EiE) delivery in marginalized areas within Somalia. Unique Contribution to Theory, Policy and Practice: Technology can be leveraged to coordinate and efficacy of response efforts. In this setting, the employment of technology to assist with data collection is critical. Digital data gathering can be vital for informing institutional-level monitoring of students' and schools' performance, impacting broader educational policy planning, and recognizing essential education requirements during times of emergency. When considering the expansion of EdTech in times of crisis, data safety and safeguarding must be prioritized.